Patient compliance with cervical smear surveillance in a shared‐care setting. Issue 2 (November 2016) - Tse, Ka Y.; Lau, Suk K.; Lui, Man W.; Ip, Philip P.; Cheung, Annie N.; Ngan, Hextan Y.
Abstract: Objective: To examine patient compliance with cervical smear surveillance at a primary care center. Methods: A retrospective study included data from patients referred from a tertiary center, to a University of Hong Kong primary care center following colposcopy for continuing cervical smear surveillance between January 1, 2005 and December 31, 2006. Patient records were reviewed and details of the initial screening or treatment that led to referral and the three subsequent follow‐up screenings were examined. A multivariate analysis was performed to identify factors that were associated with increased odds of patients not attending follow‐up screening. Results: In total, records from 833 patients were included. Of these patients, 348 (41.8%) failed to attend at least one screening, with 172 (49.4%) of this group attending after being reminded. The compliance rate prior to patients being reminded of screening follow‐up decreased across the three follow‐up screenings, with 706 (84.8%) patients attending their first follow‐up visit and 561 (67.3%) patients attending the third. In the multivariate analysis, being younger than 50 years old, having a history of smoking, and not having undergone medical treatment related to cervical cancer screening previously were associated with increased odds of not attending follow‐up screening (all P < 0.05). Conclusion: Patients at increased risk of non‐compliance with screening follow‐up should receive particular attention and counselling regarding screening.